Resistência à torção de vigas de concreto armado leve, sob a ação de cargas combinadas - Guerra, João Dourado (1973)
The purpose of this work was to determine experimentaly the failure mechanism and to verify the ultimate torsional strength of massive beams of ligthweiht reinforced concrete, of rectangular sections, containing both longitudinal and transversal reinforcements, when subjected to the combined action of torsion, bending and shear. In such a way, it was used the method of analysis developed by Lessig and others for the case of normal reinforced concrete. Nine beams were tested, having as principal variable the parameter, ratio of torsional moment to the bending moment. The tests results showed that the criterions adopted in the method of analysis utilized are also rightly applicable in the case of ligthweiht concrete.